2014
DOI: 10.1002/j.2161-1912.2014.00052.x
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to Mental Health Care: A 25‐Year Follow‐Up Study of the Orthodox Jewish Community

Abstract: The current study is a 25‐year follow‐up to a mental health needs assessment in the often overlooked, but rapidly growing, Orthodox Jewish denomination. Results suggest increased acceptance of mental illness and its treatment and satisfaction with quality of care, along with decreased mistrust of the mental health field, belief that religion and psychiatry conflict, and tendency to attach stigmas to psychiatric problems. However, issues of stigma and affordability continue to be obstacles to treatment. El pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
19
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 32 publications
1
19
1
Order By: Relevance
“…, sexuality (Ribner & Kleinplatz, 2007), and bullying (Dupper, Forrest-Bank, & Lowry-Carusillo, 2015), there remains a notable gap in the counseling literature on supporting Jewish clients (Altman et al, 2010;Ginsberg & Sinacore, 2013;Langman, 1995Langman, , 1999Schnall et al, 2014;Sue & Sue, 2016). In addition, extant articles fall short of addressing the current state of the American Jew, such as failing to account for the modern-day rise in antisemitism in the United States (Anti-Defamation League [ADL], 2013[ADL], , 2017Federal Bureau of Investigation [FBI], 2015) and issues related to Jewish identity (Goodstein, 2013).…”
Section: Issues and Insightsmentioning
confidence: 99%
See 2 more Smart Citations
“…, sexuality (Ribner & Kleinplatz, 2007), and bullying (Dupper, Forrest-Bank, & Lowry-Carusillo, 2015), there remains a notable gap in the counseling literature on supporting Jewish clients (Altman et al, 2010;Ginsberg & Sinacore, 2013;Langman, 1995Langman, , 1999Schnall et al, 2014;Sue & Sue, 2016). In addition, extant articles fall short of addressing the current state of the American Jew, such as failing to account for the modern-day rise in antisemitism in the United States (Anti-Defamation League [ADL], 2013[ADL], , 2017Federal Bureau of Investigation [FBI], 2015) and issues related to Jewish identity (Goodstein, 2013).…”
Section: Issues and Insightsmentioning
confidence: 99%
“…Furthermore, Yeung and Greenwald (1992) found that Jews were more likely to consult mental health professionals compared with Catholics and Protestants, who were more likely to seek help from medical professionals or clergy. However, even though Jews in general view help-seeking favorably, stigma remains high among Orthodox Jews (Baruch, Kanter, Pirutinsky, Murphy, & Rosmain, 2014), although the situation is improving (Schnall et al, 2014). Orthodox Jews may be more concerned with privacy and confidentiality (Loewenthal & Rogers, 2004) and tend to seek help from their rabbinical representatives rather than from mental health professionals.…”
Section: General Clinical Considerationsmentioning
confidence: 99%
See 1 more Smart Citation
“…As Rubin () recently noted: “The Jewish peoples have endured thousands of years of discrimination and subjugation, yet during this new millennium, Jews and antisemitism are conspicuously absent from university ethnic classroom discourse in the United States” (p. 1). Moreover, although Jews are often portrayed as the prototypical therapy patient—see any number of Woody Allen movies in this regard—there is a dearth of information in the professional literature on Jewish concerns, particularly on treating Jewish psychotherapy clients (Altman et al, ; Langman, , ; Schlosser, ; Schnall et al, ).…”
Section: Jews Diversity and Multiculturalism In Academiamentioning
confidence: 99%
“…There is research indicating that attitudes towards mental health difficulties in Haredi communities are changing and acceptance is evolving and there is research demonstrating the efficacy of value-and culturesensitive support groups and spiritually integrated therapies for Orthodox Jews. Yet progress is slow and there continues to be a multiplicity of issues that create barriers to accessing treatment among community members (Galloway & Byrne, 2016;Hoffman & Rossman, 2014;Loewenthal & Rogers, 2004;Schnall et al, 2014).…”
mentioning
confidence: 99%